The top 100 most cited articles on mucopolysaccharidoses: a bibliometric analysis - Liao, Ruyu; Geng, Rongrong; Yang, Yue; Xue, Yufan; Chen, Lili; Chen, Lan (Frontiers in Genetics, 2024)
Bibliometrics can trace general research trends in a particular field. Mucopolysaccharidoses (MPS), as a group of rare genetic diseases, seriously affect the quality of life of patients and their families. Scholars have devoted themselves to studying MPS's pathogenesis and treatment modalities and have published many papers. Therefore, we conducted a bibliometric and visual study of the top 100 most highly cited articles to provide researchers with an indication of the current state of research and potential directions in the field.The Web of Science Core Collection was searched for articles on MPS from January 1, 1900, to November 8, 2023, and the top 100 most cited articles were screened. The title, year of publication, institution, country, and first author of the articles were extracted and statistically analyzed using Microsoft Excel 2007. Keyword co-occurrence and collaborative networks were analyzed using VOSviewer 1.6.16.A total of 9,273 articles were retrieved, and the top 100 most cited articles were filtered out. The articles were cited 18,790 times, with an annual average of 188 citations (122-507). Forty-two journals published these articles, with Molecular Genetics and Metabolism and Proceedings of the National Academy of Sciences of the United States of America being the most published journal (N=8), followed by Pediatrics (N=7), Blood (N=6). The USA (N=68), the UK (N=25), and Germany (N=20) were the top contributing countries. The Royal Manchester Children's Hospital (N=20) and the University of North Carolina (N=18) were the most contributing institutions. Muenzer J was the most prolific author (N=14).We conducted a bibliometric and visual analysis of the top 100 cited articles in MPS. This study identifies the most influential articles currently available in the field of MPS, which provides a good basis for a better understanding of the disease and informs future research directions.